1996
DOI: 10.1139/v96-030
|View full text |Cite
|
Sign up to set email alerts
|

The photochemistry of 3,3′,4,4′-tetramethoxy-and 4-hydroxy-3,3′,4′-trimethoxystilbene — models for stilbene chromophores in peroxide-bleached, high-yield wood pulps

Abstract: The photochemistry of the title compounds has been investigated in ethanol and tetrahydrofuran solution under aerobic and anaerobic conditions. Direct irradiation of trans-3,3',4,4'-tetramethoxystilbene (tra~zs-1) in deoxygenated ethanol leads to the rapid establishment of a photostationary state with the cis isomer, and the slower formation of the ethyl ether corresponding to addition of ethanol across the olefinic C=C bond and cyclobutane dimers. The same products are formed upon photolysis in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…(The saturated solution was prepared by irradiation of a THF solution containing 0.024 M TBS-ether 1 Z with 350 nm light.) As expected, the ( E )-isomer underwent an irreversible (at 350 nm) [2 + 2] cycloaddition reaction leading to a 8.7:1 ratio of very soluble syn- and anti -cyclobutanes 2 − 5 , respectively (up to 1.0 M in hexanes, THF, ether, CH 2 Cl 2 , CHCl 3 , EtOAc). The syn- and anti - cyclobutanes were obtained as a 1:1 ratio of regioisomers (Figure ).…”
supporting
confidence: 67%
“…(The saturated solution was prepared by irradiation of a THF solution containing 0.024 M TBS-ether 1 Z with 350 nm light.) As expected, the ( E )-isomer underwent an irreversible (at 350 nm) [2 + 2] cycloaddition reaction leading to a 8.7:1 ratio of very soluble syn- and anti -cyclobutanes 2 − 5 , respectively (up to 1.0 M in hexanes, THF, ether, CH 2 Cl 2 , CHCl 3 , EtOAc). The syn- and anti - cyclobutanes were obtained as a 1:1 ratio of regioisomers (Figure ).…”
supporting
confidence: 67%
“…One of the most lucid proposals regarding the type of chromophores involved suggests that the yellowing results from the formation of o -quinones from diguaiacylstilbenes. These stilbenes are generated during the mechanical grinding, disc refining, and alkaline peroxide treatment of spruce pulps. The precursors of the stilbenes, in turn, are diarylpropane units of lignin, i.e., fragments of the amorphous lignin polymer that together with cellulose and hemicellulose makes up the main fraction of the wood fiber cell wall. In the context of this proposal, polyalkylated stilbenes have been shown to be important chromophores, , and it has been suggested that these compounds undergo photoinduced redox and degradation reactions producing phenoxy-type radicals that in turn react further to form the corresponding o -quinones with absorption characteristics yielding a yellow coloration.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment reported in Figure was started in the spectrophotometric cell compartment and the reaction progress monitored in the early stages. After 40 s the cuvette was removed from the spectrophotometer and rapidly introduced into a photoreactor, where it was irradiated for 30 s . The cuvette was then rapidly reintroduced into the spectrophotometer and the reaction progress monitored until reaction completion.…”
Section: Resultsmentioning
confidence: 99%